ASSET MANAGEMENT STRATEGY FOR VILLAGE OWNED COMPANIES IN THE FRAMEWORK OF INCREASING VILLAGE REVENUE - Andhika Ligar Hardika; Paulus Sugianto Yusuf; Rini Susiani; Supriyanto Ilyas; Syafdinal Syafdinal (Jurnal Ekonomi, 2023)
This research aims to succeed in village development by increasing village income. Describe how Village Owned Enterprises carry out that asset management strategy in increasing village income. By explaining the inhibiting factors for the development of Village-Owned Enterprises in running their business and providing solutions in the form of strategies to develop Village-Owned Enterprises, the asset management strategy implemented includes observing the environment, preparing strategies, implementing strategies, and evaluating or controlling. The method used in this study is a qualitative method with a descriptive approach through interviews. The research results obtained are Village Owned Enterprises experiencing several problems, namely the level of public awareness, access to capital, marketing, and human resources. Some of the strategies implemented are outreach to the public to increase awareness, increase and optimize business profit results with strengthened financial reports to convince borrowers of capital, cooperate with outsiders, and provide training to improve human resource performance.